2018
DOI: 10.3390/su10124723
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Private Investors Conduct Strategies by Governments Supervising Public-Private Partnership Projects in the New Media Era

Abstract: Private investors and governments need to cooperate in public-private partnership (PPP) projects but the private investors may be in pursuit of their own profit by conducting defaulting behaviors which causes various environmental problems and economic risks. However, the information asymmetry between them makes it difficult to supervise the behaviors of private investors. The development of internet and social media creates new environment for the information spread and people are using new media increasingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Fang suggested a PPP program which encourages investment companies to cooperate with residents to promote the usage of solar power, and an evolutionary game model was established considering three populations [18]. Wang found that the public engagement through new media, government reputation, incentive mechanism, the discovering probability of defaulting behaviors and the punishment measures were the main factors for the private investors to make decision on the defaulting behaviors [19]. Guo and Li found that the government, the public, and investors could finally reach a balanced state of government supervision, owners' participation, and private sectors effort.…”
Section: Introductionmentioning
confidence: 99%
“…Fang suggested a PPP program which encourages investment companies to cooperate with residents to promote the usage of solar power, and an evolutionary game model was established considering three populations [18]. Wang found that the public engagement through new media, government reputation, incentive mechanism, the discovering probability of defaulting behaviors and the punishment measures were the main factors for the private investors to make decision on the defaulting behaviors [19]. Guo and Li found that the government, the public, and investors could finally reach a balanced state of government supervision, owners' participation, and private sectors effort.…”
Section: Introductionmentioning
confidence: 99%
“…We used the withdrawn project data to investigate which factors led to the initiation of inappropriate PPP projects by local governments. Most of the literature focuses on how microlevel factors, such as contract design, affect the performance of PPP projects [12,13], while only a small number of empirical studies investigate the impact of macrolevel factors on PPP development, especially whether local governments choose to adopt PPP in local infrastructure development. To the best of our knowledge, we provide one of the first empirical insights into local governments' PPP adoption.…”
Section: Introductionmentioning
confidence: 99%
“…However, the correlation could weaken contract control and adjustment. Wang et al found that the opportunistic behavior of investors influenced by public engagement, government reputation, incentive mechanism, discovery probability of opportunistic behavior, and penalty measures [58]. Since opportunistic behavior is not conducive to the healthy and sustainable partnership of both parties in MSW disposal PPP projects, effective governance mechanisms, such as contracts, are needed to govern investors' opportunistic behavior [59].…”
Section: Literature Reviewmentioning
confidence: 99%